2021
DOI: 10.1002/uog.23650
|View full text |Cite
|
Sign up to set email alerts
|

Fusion imaging in preoperative assessment of extent of disease in patients with advanced ovarian cancer: feasibility and agreement with laparoscopic findings

Abstract: What are the novel findings of this work? Fusion of computed tomography (CT) and ultrasound images is feasible in patients with suspicion of ovarian or peritoneal cancer. It can improve the accuracy, as compared with surgical findings, of both CT and ultrasound alone in the preoperative mapping of pelvic and abdominal disease. What are the clinical implications of this work?Improved preoperative evaluation of the extent of intra-abdominal disease in ovarian cancer patients by fusion imaging compared with CT (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The Cohen's Kappa agreement analysis was used in the present study as well as other research as well with finding similar results as of this study 19 . There was a strong agreement in the results of the laparotomy with the ultrasound results 20 .…”
Section: Discussionsupporting
confidence: 71%
“…The Cohen's Kappa agreement analysis was used in the present study as well as other research as well with finding similar results as of this study 19 . There was a strong agreement in the results of the laparotomy with the ultrasound results 20 .…”
Section: Discussionsupporting
confidence: 71%
“…Several recent studies have highlighted the potential value of fusion imaging for some gynecological cancers 7 , 9 , 10 , 16 . These studies suggested that fusion of MRI or CT and ultrasound is feasible in patients with locally advanced cervical or ovarian cancer and may increase the diagnostic accuracy relative to that of the individual imaging methods used alone 10 , 16 .…”
Section: Indications For Fusion Imaging In Gynecologymentioning
confidence: 99%
“…However, the MRI‐ultrasound fusion technique is underdeveloped in the field of obstetrics and gynecology. Preliminary studies have suggested its potential in identifying deep pelvic endometriosis and Cesarean section scars 5 , 6 , and more recent studies have also underlined the potential value of fusion of CT or 19 FDG‐PET with ultrasound in the evaluation of gynecological cancers 7 , 8 , 9 , 10 . In order to determine the potential contribution of MRI‐ultrasound fusion, since 2019, we have undertaken to apply it to 160 patients with suspected endometriosis selected to undergo joint investigation by MRI and transvaginal ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a growing interest in offline fusion imaging, which refers to a-posteriori merging of two different imaging modalities [4][5][6][7][8][9] . We aimed to merge two 3D ultrasound volumes to create a single complete dataset of the entire brain in three orthogonal planes with consistent quality and spatial resolution throughout, allowing exploration of the central nervous system anatomy.…”
mentioning
confidence: 99%